STATE-OWNED ENTERPRISES AND ECONOMIC CONSTITUTIONS: A CASE STUDY OF JUDICIAL REVIEW OF LAW NO.19 OF 2003 - Trihatmoko, R. Agus (Jurnal Hukum dan Peradilan, 2019)
The purpose of this study seeks to uncover the meaning of Law No. 19 of 2003 and Article 33 of the 1945 Constitution of the Republic of Indonesia, and identify the essence of the roles and functions of SOEs in implementing the economic constitution. The study of SOEs in the realm of constitutional economics is seen as very important as a reflection of the rapid change in national and global economic development. The findings of the study lead to the philosophical understanding of economic constitution for the Republic of Indonesia by the role of state companies in national economic development. The theoretical description of the results of this study contributes to the knowledge of political economy and political democracy. The benefits practically have implications for the practice of public management about the governance of state enterprises, as well as corporate management for SOEs or other state-owned companies.